2022
DOI: 10.1021/acs.iecr.2c01352
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of a Simulated Moving Bed Reactor for the Synthesis of Solketal by Implementing Multifeed Strategy

Abstract: The simulated moving bed reactor (SMBR) is a sorption-enhanced reactive technology that has been successfully applied to the synthesis of several organic compounds, due to its ability to overcome the thermodynamic limitations associated with reversible reactions. This work proposes the implementation of an innovative multifeed strategy that can considerably improve the performance of the SMBR, particularly for systems in which none of the reactants can be used as desorbent. A systematic design methodology base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
(107 reference statements)
0
0
0
Order By: Relevance
“…Previous studies have shown that, if an efficient process integration strategy is achieved and the eluent is recirculated to the process, production costs could be decreased by 44% compared to conventional processes [243]. Subsequently, the same authors carried out a process improvement, finding that, under optimum conditions, the maximum productivity is 10 kg of solketal per liter of adsorbent per day, with the desorbent (ethanol) consumption being below 6 L per kg of solketal produced [244].…”
Section: Latest Technological Advancesmentioning
confidence: 99%
“…Previous studies have shown that, if an efficient process integration strategy is achieved and the eluent is recirculated to the process, production costs could be decreased by 44% compared to conventional processes [243]. Subsequently, the same authors carried out a process improvement, finding that, under optimum conditions, the maximum productivity is 10 kg of solketal per liter of adsorbent per day, with the desorbent (ethanol) consumption being below 6 L per kg of solketal produced [244].…”
Section: Latest Technological Advancesmentioning
confidence: 99%